Study of definitive surgical management of patients with corrosive stricture of upper gastrointestinal tract - Vaidya, Bina; Desai, Meet; Patel, Tejas; Tulsiyani, Chirag; Singh, Rajkumar; Sesodia, Rohit (International Surgery Journal, 2020)
Background: Corrosive injury of the oesophagus and stomach is a cause of major morbidity and mortality and is usually seen in the younger age group. Although definitive surgical procedures are available, there is a considerable debate on the timing of a definitive surgery and its electiveness. This study aims to document the benefits of elective surgery and the outcomes of various surgical procedures. Methods: A retrospective observational study of 25 cases of corrosive stricture of upper gastrointestinal tract who underwent definitive surgical procedure was conducted in the department of general surgery at the new civil hospital and government medical college, Surat during a period of 60 months from July 2014 to July 2019. Patients were followed up till a period of 6 months post definitive surgical procedure and were evaluated. Results: Out of 25 patients in our study subjected to definitive surgical procedure in the form of either gastrojejunostomy (GJ) or colonic transposition, 18 patients (72%) could take fully oral and required no further intervention till 6 months post-operative follow up; 3 patients (12%) due to post-operative oesophageal stricture required serial 3 monthly oesophageal dilatation with controlled radial expansion (CRE) balloon; 4 patients (16%) had expired. Conclusions: The choice of definitive surgical procedure according to the level of oesophageal stricture and its optimal timing gives good outcomes with less morbidity and mortality in patients with corrosive substance ingestion.